Elimination of Escherichia coli and Salmonella in Clam by Using Zeolite in a Station of Depuration: Gdoura et al. (1st September 2017) - Gdoura, Morsi; Sellami, Hanen; Khannous, Lamia; Ketata, Najib; Neila, Idriss Ben; Traore, Al Ibrahim; Chekir, Zouhair; Gdoura, Radhouane
ABSTRACT: : The application of natural zeolite for water and wastewater treatment has been carried out and is still a promising technique in environmental cleaning processes. Natural zeolite can be used to improve the purification process of clams ( Ruditapes decussatus ). Thus, our study aimed at improving the clam purification system in order to reduce Escherichia coli and eliminate Salmonella in samples artificially contaminated with this bacterium using a natural zeolite to replace the biological filter. The results showed that zeolite used in a depuration system improved the clam purification process. Moreover, natural zeolite exhibited high performance in the adsorption of bacteria and allowed to reduce the Escherichia coli abundance in 24 h, thus ensuring purified clams conformity with the ISO 16649‐3 standard. These results indicate the beneficial effects of using zeolite in the adsorption of bacteria and the reduction in the abundance of Escherichia coli and set the Salmonella from marine organisms.